2012
DOI: 10.1556/aagr.60.2012.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weather conditions on variability in sunflower yield over years in eastern parts of Croatia and Hungary

Abstract: Oil crops constitute the second most important field crops worldwide and are important both in Hungary and Croatia. Among the oil crops, sunflower has a significant role in Hungary (~550,000 ha) and Croatia (~30,000 ha). The main aim of this study was to compare sunflower yields and their variation over years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) in the eastern parts of Hungary and Croatia, with the emphasis on the impact of rainfall and temperature regime, and using a rain factor (RFm) calculated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…For sunflower, our results proved that 61% of its yield change variation could be due to climatic variables. This result corroborates the findings of Mijić et al [67], who indicated that rainfall before and during the vegetation period has a great effect on sunflower yield.…”
Section: Discussionsupporting
confidence: 92%
“…For sunflower, our results proved that 61% of its yield change variation could be due to climatic variables. This result corroborates the findings of Mijić et al [67], who indicated that rainfall before and during the vegetation period has a great effect on sunflower yield.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 96 sunflower genotypes (36.9% of the total) had significantly less PSC than the susceptible check HA 89 (28.1% PSC DI). Hungary is situated in the temperate zone and is affected by three large climatic zones: the Atlantic, continental, and Mediterranean (Anonymous, 2008 and mean temperature ranged between 16.8 and 17.3°C during the vegetative growth period (Mijic´ et al, 2012). The majority of the resistant PIs were received from Hungary (14) and Spain (9).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, nine of these 13 PIs were landraces received from Hungary, possibly indicating that a "hotspot" of disease-resistant germplasm developed there. Hungary is situated in the temperate zone and is affected by three large climatic zones: the Atlantic, continental, and Mediterranean (Anonymous, 2008 and mean temperature ranged between 16.8 and 17.3°C during the vegetative growth period (Mijic´ et al, 2012). This temperature range is ideal for both S. sclerotiorum and P. helianthi, while the splashing rain helps disseminate spores and initiate the infection process (Gulya et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The level of varieties' and hybrids' biological potential realization depends on both-growing technology and climatic conditions of a particular year and their interaction [21] [22] [23] [24]. Sunflower yield is determined by several factors, among which the role of hybrid and plants' standing density are among the determinants [25] [26].…”
Section: Morphological Features Of Plants Sunflower Yield Depending On Plants' Densitymentioning
confidence: 99%